Al-doped silica nanospheres supported Ni catalyst for active sites modulating in the reductive depolymerization of technical lignin - Nan Wang; Yaxin Deng; Zhijie Liao; Qiyu Liu; Jianglin Liu; Xuliang Lin; Zhenyao Wang; Xueqing Qiu (Chemical Engineering Journal, 2026)

Study on the adsorption of common antibiotics in water by cellulose-based adsorbents derived from sugarcane bagasse - Jiarong Jin; Xuliang Lin; Chak Yin Tang; Wing Cheung Law; Ruchun Wu; Lei Zhong (Process Safety and Environmental Protection, 2025)

Observation of Low-Level Jets in the Eastern Tropical Indian Ocean Based on Shipborne Coherent Doppler Lidar - Haiyuan Wang; Lin Liu; Mengqi Fan; Yang Yang; Guang Yang; Yongliang Duan; Baochao Liu; Qinglei Su; Binbin Zhang; Fengjun Wang; Xuliang Shi; Qiuchi Li; et al. (Journal of Ocean University of China, 2024)

Micro-helical Ni3Fe chain encapsulated in ultralight MXene/C aerogel to realize multi-functionality: Radar stealth, thermal insulation, fire resistance, and mechanical properties - Sen Lin; Jing Lin; Zhiqiang Xiong; Xue He; Xin Li; Chongbo Liu; Chengying Wang; Xiaojun Zeng; Xuliang Nie; Renchao Che (Chemical Engineering Journal, 2024)

Structure regulation of lignin-derived N-doped carbon-supported Ni catalyst for efficient upgrading of ethanol to higher alcohols - Quanzhou Xu; Xing Fei; Xueqing Qiu; Xiaofei Wang; Tiejun Wang; Xuliang Lin; Sha Li; Yanlin Qin (Chemical Engineering Journal, 2024)

Zeolite structure descriptor for guiding the synthesis of efficient titanosilicalites through matching Ti sites and framework topologies for 1-Hexene epoxidation - Xuliang Deng; Dong Lin; Yang Xu; Xiang Feng; De Chen; Chaohe Yang; Honghong Shan (Chemical Engineering Journal, 2024)

Lignin-derived hierarchical porous carbon with high surface area and interconnected pores for efficient antibiotics adsorption - Jingyu Wang; Dezhe Fan; Lizhu Zhang; Dongjie Yang; Xueqing Qiu; Xuliang Lin (Chemical Engineering Journal, 2023)

Construction of anodic electron transfer chain based on CuCl2/TiOSO4 synergetic mediators for highly efficient conversion of biomass wastes into electricity at low temperature - Chenxing She; Xihong Zu; Zhiheng Yang; Liheng Chen; Zixin Xie; Hao Yang; Dongjie Yang; Guobin Yi; Yanlin Qin; Xuliang Lin; Wenli Zhang; Huafeng Dong; et al. (Chemical Engineering Journal, 2023)

Feasibility Research on Fish Pose Estimation Based on Rotating Box Object Detection - Bin Lin; Kailin Jiang; Zhiqi Xu; Feiyi Li; Jiao Li; Chaoli Mou; Xinyao Gong; Xuliang Duan (Fishes, 2021)
A video-based method to quantify animal posture movement is a powerful way to analyze animal behavior. Both humans and fish can judge the physiological state through the skeleton framework. However, it is challenging for farmers to judge the breeding state in the complex underwater environment. Therefore, images can be transmitted by the underwater camera and monitored by a computer vision model. However, it lacks datasets in artificial intelligence and is unable to train deep neural networks. The main contributions of this paper include: (1) the world’s first fish posture database is established. 10 key points of each fish are manually marked. The fish flock images were taken in the experimental tank and 1000 single fish images were separated from the fish flock. (2) A two-stage attitude estimation model is used to detect fish key points. The evaluation of the algorithm performance indicates the precision of detection reaches 90.61%, F1-score reaches 90%, and Fps also reaches 23.26. We made a preliminary exploration on the pose estimation of fish and provided a feasible idea for fish pose estimation.

Pretreatment of Miscanthus by NaOH/Urea Solution at Room Temperature for Enhancing Enzymatic Hydrolysis - Hongming Lou; Qiaoyan Hu; Xueqing Qiu; Xiuli Li; Xuliang Lin (BioEnergy Research, 2016)